On One Minkowski–Radon Problem and Its Generalizations - Volchkov, V. V.; Savost’yanova, I. M. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
We study functions on a sphere with zero weighted means over the circles of fixed radius. A description of these functions is obtained in the form of series in special functions.